Simulations of hydraulic fracturing initiation in perforated boreholes - Fallahzadeh Abarghooei, Syed Hassan (Curtin University, 2015)
The mechanism of initiation and propagation of hydraulic fracture from cased hole perforated wellbores is investigated through analytical, numerical and experimental studies. A new model was developed for arbitrarily oriented wellbore and perforation to predict the fracture initiation pressure, location and orientation, along the perforation length. In addition, scaled experimental and numerical studies were carried out to validate the analytical model and to investigate the effects of fluid viscosity and injection rate on fracture geometry.